A influ??ncia da disfun????o er??til na qualidade de vida de homens com c??ncer de pr??stata - Pontes, Shirley (2018)
The diagnosis and treatment of prostate cancer can cause significant changes in the life of men influencing their quality of life. The objective of this study was to evaluate the health-related quality of life of patients with prostate cancer submitted to radiotherapy. It is a descriptive cross-sectional study with non-probabilistic sampling. Subjects eligible for the study were 120 men with prostate cancer who underwent on treatments at HUB - CACON. The instruments used were EORTC QLQ-C30 and the International Index Of Erectil Function- IIEF-5. The research project was approved by the Ethics and Research Committee of the Faculty of Medicine of the Catholic University of Brasilia under the number CAAE: 58197916.8.0000.0029.: The profile os subjects is aged between 70 and 79 years (42.3%), with elementary school (72.3%), brown (44.6%), married or had a partner (75.6%). Among the comorbidities, the highest incidence was arterial hypertension (70%) followed by Diabetes MellitusII (33.8%). The most frequent toxicities resulting from RT treatment, was dysuria (43%), followed by diarrhea (22.3%). The analysis of IIEF-5 allows to observe that 79.2% suffer from severe erectile dysfunction.. The prostate cancer treatments tend to cause negative impacts on sexual function and self-perceived quality of life. The age does not influence role performance, and isolated or simultaneous treatments proved to be important factor to erectile function score. Conclusion: The group who have undergone to RT + RP suffer more from pain and fatigue, and the group who have undergone to RT + CQ suffer more insomnia. All participants who have undergone RT + PR + CQ suffer severe erectile dysfunction. Considering the findings of this study, it confirm that the patients with prostate cancer who manage maintain erectile function moderate, mild and normal, they as well maintain their social roles as work, family relationships and marriage. They also keep their emotions balanced and control their irritability, tension, depression, and they feel less fatigue. This study allows to understand the local reality and corroborates with the findings of other studies carried out in different regions and social contexts.